Analisis Pengelolaan Biaya Operasional Terhadap Profitabilitas Pada Perusahaan Umum (PERUM) DAMRI Cabang Manado - Rambalangi, Suchi Maranatha; Festus Rombot, Raymond; Pesik, Heidy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the management of operational costs in relation to profitability at the Manado Branch of Perum DAMRI. The management of operational costs—specifically regarding fuel and vehicle maintenance expenses—is a critical aspect of the company’s sustainability; effective cost management enhances corporate performance, enabling the company to achieve objectives such as generating profit. Profitability serves as a key indicator of earnings, making cost management and control essential for maintaining the company’s operational stability. This study employs a qualitative approach and a descriptive method, utilizing data collection techniques that include observation, interviews, and documentation. The findings indicate that while cost management is practiced—specifically through the control of fuel consumption and routine fleet maintenance—the current monitoring system remains conventional. Furthermore, the company needs to consistently implement preventive maintenance, periodically evaluate operational costs, and enhance driver competence through eco-driving training.